The knowledge mapping of traditional Chinese medicine for hepatocellular carcinoma: A bibliometric study - Wenya Pei; Boyu Jiao; Zexiong Chen; Jingchun Zeng; Yancheng Fu; Zhanmou Liang; Baoguo Sun; Jingwen Ruan; Shijun Zhang (Pharmacological Research - Modern Chinese Medicine)
Introduction: Traditional Chinese medicine is widely used as adjuvant therapy for hepatocellular carcinoma (HCC), but no relevant bibliometric study has comprehensively analyzed the available data. Methods: To summarize the research landscape of traditional Chinese medicine (TCM) in relation to HCC over the past decade, publications on TCM and HCC from 2013 to 2023 were collected and analyzed using CiteSpace software. Results: A total of 1,160 articles on TCM for HCC were included in the bibliometric analysis, with the most productive countries and institutions located in the Asia region. The analysis indicated that traditional Chinese medicine may enhance immunity and regulate the local tumor microenvironment through mechanisms involving DNA damage, cell cycle arrest, and apoptosis by signaling pathways. Discussion: This study provides insights into the trends of traditional Chinese medicine for hepatocellular carcinoma, which may inform clinical practice and identify potential targets for further research. However, high-quality evidence-based research and rigorous mechanistic studies should be prioritized to explore new anticancer approaches.